The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5603/gp.2016.0035
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ultrasound and Doppler parameters in the third trimester of pregnancy as predictors of adverse perinatal outcome in unselected pregnancies

Abstract: Objectives: The aim of the study was to investigate ultrasound and Doppler parameters in the third trimester of pregnancy as possible predictors of adverse perinatal outcome in unselected pregnancies. Material and methods:We performed a retrospective cross-sectional study including unselected pregnant women between 27 and 36 + 6 weeks of gestation. The following ultrasound and Doppler parameters were assessed: estimated fetal weight (EFW) [g], EFW percentile, placental maturity grade (Grannum classification), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Yet, a major weakness of their study is a relatively small group of only 24 patients that were enrolled to the cohort. Recent studies, in contrast, investigate the power of Doppler parameters in predicting adverse perinatal outcomes using non-selected groups of patients, where the included complications, like small gestational age (SGA), fetal growth restriction (FGR), gestational hypertension or gestational diabetes mellitus, could influence significantly the results (2,9,12,14,16,18,(21)(22)(23) . In our study, we found no significant correlation of Doppler parameters with Apgar score < 7 at 1 min.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a major weakness of their study is a relatively small group of only 24 patients that were enrolled to the cohort. Recent studies, in contrast, investigate the power of Doppler parameters in predicting adverse perinatal outcomes using non-selected groups of patients, where the included complications, like small gestational age (SGA), fetal growth restriction (FGR), gestational hypertension or gestational diabetes mellitus, could influence significantly the results (2,9,12,14,16,18,(21)(22)(23) . In our study, we found no significant correlation of Doppler parameters with Apgar score < 7 at 1 min.…”
Section: Discussionmentioning
confidence: 99%
“…First, we examined a select group of fetuses with suspected CoA, referred to two tertiary centers for fetal echocardiographic studies. While national obstetrics screening protocols often suggest that first-and second-trimester ultrasound examinations are offered to all pregnant women, it may be advantageous to perform third-trimester screening to examine the heart for late-onset cardiac malformations such as CoA, as well as abnormal fetal growth [35][36][37][38][39][40] . Second, the coefficients from the logistic regression equation were derived from measurements of the 4CV and speckle-tracking analysis of the ventricles using the protocol described herein and, until recently, the software for computing the Z-scores used in this study was under experimental protocol and not commercially available.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Intrauterine growth restriction (IUGR) is an important clinical problem, being the most important cause of perinatal morbidity and mortality [6] . Abnormal Doppler findings in the third trimester are usually associated with adverse perinatal outcome [7,8] .…”
Section: Introduction the Introduction Of Colour Doppler Velocimetry To Obstetrics Offers A Non Invasive Methods Formentioning
confidence: 99%